Prevalence of bovine viral diarrhea, bovine neosporosis, enzootic bovine leukosis and bovine paratuberculosis in dual-purpose cows in conditions of the - Naranjo Guerrero, Luisa Fernanda (2022)
The aim of this study was to determine the prevalence of bovine viral diarrhoea (BVD), bovine neosporosis (NEOS), enzootic bovine leukosis (EBL) and bovine paratuberculosis (BP) in dual-purpose cows reared under low-tropic conditions. The study was carried out at La Pintada farm located in the municipality of Puerto Boyacá, Boyacá, Colombia, taking blood samples from 840 2–3-year-old cows collected from various departments of the country. Competitive (BVD, NEOS, EBL) and indirect (BP) ELISA tests were performed. A seropositivity of 25.83% to BVD, 16.29% to NEOS, 14.64% to EBL and 4.17% to BP was found.